FACTORS INFLUENCING STUDENTS’ COST OF LIVING: EVIDENCE FROM MALAYSIAN UNIVERSITIES (International Journal of Banking and Finance, 2024)
It is widely evident that cost of living among university students are increasing over time. That said, little is understood about factorsassociated with general expenses among students in Malaysian universities. The present study uses primary survey data (n = 454)to examine the correlates of the total amount of money spent by students in a month. An ordered regression model was used to shedlight on factors contributing to different magnitudes of expenses. The explanatory variables consisted of demographic factors, financial knowledge, parental income, peer influence, and personality trait of conscientiousness. Findings from the present study showed that a large proportion of students spent between Ringgit Malaysia (RM) 201 and RM400 per month. Young, male students tended to spend more than older, female students. Expenditure was higher among Chinese students than Malays. Educational levels and income were found to correspond to spending. Having good financial knowledge was associated with reduced expenditure. Students who were influenced by their peers were likely to indulge in high spending compared to those who were not. These findings have important implications for strategic planning and to assist policymakers, parents, and university authorities in formulating better intervention measures aimed at improving students’ spending behaviour, thereby lowering cost of living.